Phaeohyphomycosis Caused by Phaeoacremoniumrubrigenum in an Immunosuppressive Patient: A Case Report and Review of the Literature - Sadanori Furudate; Shu Sasai; Yukikazu Numata; Taku Fujimura; Setsuya Aiba (Karger Publishers, 2012)
Phaeohyphomycosis (PHM) is a rare, deep fungal infection of the skin and subcutaneous tissues caused by dematiaceous fungi. In this report, we describe a case of PHM caused by Phaeoacremoniumrubrigenum, which is generally known to infect woody plants. We detected the gray-blackish villi by biopsy culture material, and slide culture revealed the conidia arising from slightly tapering phialides. Furthermore, we differentiated these fungi as P.rubrigenum by Basic Local Alignment Search Tool (BLAST) algorithm. We performed surgical debridement of disseminated nodules and administered oral itraconazole for a duration of 4 weeks. One year after stopping itraconazole, there was no sign of relapsing subcutaneous nodules. To our knowledge, this is the third case report of PHM developing from skin infection by P. rubrigenum in human.